Empowerment Of The Agribusiness Sector As A Effort To Increase Food Security (Artikel Review) - Fikriman Fikriman; Nini Mawaddah Haryadi; Pitriani Pitriani (Fakultas Pertanian Universitas Muara Bungo, 2022)
The agribusiness sector is a mega sector in the national economy, involving all national regions, involving and supporting about 80 percent of the Indonesian population, absorbing most of the national workforce with various qualities and various socio-cultural backgrounds. As an effort to increase food security, it is necessary to empower the agribusiness sector. The food crisis cannot be solved only in the sub-sector, but must be comprehensive starting from upstream agribusiness, farming, and downstream food, including the provision of supporting services. As part of the national economy, the performance of the agribusiness sector is influenced by the economic strategies and policies adopted by the government. The purpose of this paper is to discuss the relationship between empowerment of the agribusiness sector, especially as an effort to increase food security. Since the economic crisis hit, only the domestic agribusiness sector has been able to survive, therefore to make adjustments to the new environment, namely by empowering the agribusiness economic sector as a national industrialization strategy that is able to build a strong foundation of Indonesia's balance of payments in the long term and able to survive, especially in the long term. food crisis period that has the potential for national economic recovery.